2000
DOI: 10.1016/s0168-6496(00)00024-6
|View full text |Cite
|
Sign up to set email alerts
|

Carbofuran degradation mediated by three related plasmid systems

Abstract: Two carbofuran-metabolizing Sphingomonas strains, TA and CD, were isolated from soils with differing histories of exposure to carbofuran. These strains were compared with a previously described strain, Sphingomonas sp. CFO6, with regard to growth rate, formation of metabolites, and plasmid content and structure. Extensive regions of similarity were observed between the three different plasmid systems as evidenced by cross hybridization. In addition, all three systems harbor IS1412, an insertion sequence (IS) e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The presence of five different plasmids in Sphingomonas sp. MM‐1 clearly demonstrated that there must exists at least five different incompatibility groups in sphingomonads, and it can be assumed that the pronounced rearrangements, which occur after the conjugative transfer of degradative plasmids among sphingomonads, might be (at least in certain cases) related to incompatibility phenomena (Feng et al ., , b; Ogram et al ., ; Basta et al ., , ). The phenotypically defined incompatibility groups can be correlated with the sequences of the replication initiator (Rep) proteins and the proteins involved in plasmid partition (Par) (Petersen, ).…”
Section: Comparison Of the Replication Initiation (Rep) Proteins Encomentioning
confidence: 98%
See 1 more Smart Citation
“…The presence of five different plasmids in Sphingomonas sp. MM‐1 clearly demonstrated that there must exists at least five different incompatibility groups in sphingomonads, and it can be assumed that the pronounced rearrangements, which occur after the conjugative transfer of degradative plasmids among sphingomonads, might be (at least in certain cases) related to incompatibility phenomena (Feng et al ., , b; Ogram et al ., ; Basta et al ., , ). The phenotypically defined incompatibility groups can be correlated with the sequences of the replication initiator (Rep) proteins and the proteins involved in plasmid partition (Par) (Petersen, ).…”
Section: Comparison Of the Replication Initiation (Rep) Proteins Encomentioning
confidence: 98%
“…observed for the degradative pathways of γ‐hexachlorocyclohexane or dibenzo‐ p ‐dioxin) or are at least organized in several transcriptional units (Stolz, ). Furthermore, these plasmids often undergo after transfer between different sphingomonads pronounced rearrangements (Feng et al ., , b; Ogram et al ., ; Basta et al ., , ). Therefore, it seems that the maintenance, transfer and recombination of these plasmids are of major importance for the exceptional degradative capabilities of this group of bacteria.…”
Section: Introductionmentioning
confidence: 98%
“…Many sphingomonads degrade naphthalene, phenanthalene, and anthracene via common pathways found in other gram‐negative bacteria (Pinyakong et al , 2003a, b). It was demonstrated that large plasmids present in xenobiotic‐degrading Sphingomonas strains are responsible for the degradative capabilities (Kim et al , 1996; Feng et al , 1997; Romine et al , 1999; Ogram et al , 2000; Basta et al , 2004). For example, a 40‐kb DNA region was found to be related to aromatic catabolism in Sphingobium yanoikuyae strain B1, in which two dioxygenase genes are predicted to be required for conversion of PAHs and biphenyl to simple aromatic acid, and meta ‐cleavage genes are required for conversion of aromatic acids to the tricarboxylic acid cycle (TAC) intermediate (Yen & Serdar, 1988; Assinder & Williams, 1990; Zylstra & Kim, 1997; Kim & Zylstra, 1999).…”
Section: Bacterial Catabolism Of Polycyclic Aromatic Hydrocarbonsmentioning
confidence: 99%
“…Several bacteria capable of degrading carbofuran have been isolated and characterized [6–8]. Microorganisms utilize carbofuran by hydrolysis of labile methylcarbamate linkage, yielding carbofuran‐7‐phenol and methylamine [6].…”
Section: Introductionmentioning
confidence: 99%